Children’s Spatial Representations: 3- and 4-Year-Olds are Affected by Irrelevant Peripheral References - Krüger, Markus; Jahn, Georg (Frontiers in Psychology, 2015)
Children as young as 3 years can remember an object’s location within an arrangement and can retrieve it from a novel viewpoint (Nardini, Burgess, Breckenridge, & Atkinson, 2006). However, this ability is impaired if the arrangement is rotated to compensate for the novel viewpoint, or, if the arrangement is rotated and children stand still. There are two dominant explanations for this phenomenon: Self-motion induces an automatic spatial updating process which is beneficial if children move around the arrangement, but misleading if the children’s movement is matched by the arrangement and not activated if children stand still and only the arrangement is moved (see spatial updating; Simons & Wang, 1998). Another explanation concerns reference frames: Spatial representations might depend on peripheral spatial relations concerning the surrounding room instead on proximal relations within the arrangement, even if these proximal relations are sufficient or more informative. To evaluate these possibilities, we rotated children (N = 120) aged between 3 and 6 years with an occluded arrangement. When the arrangement was in misalignment to the surrounding room, 3- and 4-year-olds’ spatial memory was impaired and 5-year-olds’ was lightly impaired suggesting that they relied on peripheral references of the surrounding room for retrieval. In contrast, 6-years-olds’ spatial representation seemed robust against misalignment indicating a successful integration of spatial representations.